Digital Trust and Brand Origins: The Impact of Online Customer Reviews and Country of Origin on Skincare Purchase Intentions in E-Commerce - Asani, Nurlina Putri; Wonua, Andry Stepahnie Titing, Almansya Randu (Pascasarjana STIE Amkop Makassar, 2025)
The rapid expansion of e-commerce has transformed consumer purchasing behavior, particularly in the beauty and skincare industry, where online product evaluations play a crucial role in shaping purchase decisions. This study examines the influence of online customer reviews (OCR) and country of origin (COO) on purchase intention for Skintific skincare products through Shopee in Southeast Sulawesi. Utilizing a quantitative research approach, data were collected from 120 respondents through an online and offline survey, employing a Likert-scale questionnaire. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess both the measurement model and structural model. The findings reveal that OCR significantly and positively influences purchase intention, with key dimensions such as Perceived Usefulness, Source Credibility, Valence, and Argument Quality playing a crucial role. Additionally, COO has a strong and significant impact on purchase intention, with consumer perceptions of Innovation, Design, Quality, and Prestige shaping their product evaluations. These results align with prior studies emphasizing the growing importance of electronic word-of-mouth (eWOM) and COO branding in digital consumer behavior. The study contributes to the literature by integrating OCR and COO into a unified consumer decision-making framework, providing valuable insights for brands and e-commerce platforms to optimize their marketing strategies. Future research is encouraged to explore moderating factors such as brand familiarity, consumer trust, and cultural influences to further understand the complexities of online purchasing behavior in emerging markets. Keywords:Online Customer Reviews, Country of Origin, Purchase Intention, E-commerce, Skincare Industry, PLS-SEM